Pertumbuhan dan Produksi Jagung Manis yang Ditumpangsarikan dengan Kacang Tunggak pada Lahan Pasca Tambang Batu Andesit - Salsabila; Heni Purnamawati; Munif Ghulamahdi (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2022)
Revegetation is an effort to improve soil conditions and increase the ecological and economic value of the ex-mining soil through the addition of organic matter and planting. This study evaluates the growth, production, and land equivalence ratio of sweet corn intercropped with cowpea on land after andesite mining. The experiment was conducted on the ex-mining land of PT. Diaz Pratama Utama, Serang Regency, Banten, from March to June 2020. This experiment used a completely randomized factorial design and four replications. The first factor was the number of intercropping rows (one or two rows of cowpea), and the second factor was the dose of goat manure (0, 5, 10, and 15 ton ha-1). The results showed that an application of 10 ton ha-1 goat manure with two rows of intercropped cowpea had resulted in the best sweet corn growth and the highest sweet corn yield of 12.2 ton ha-1. Intercropping sweet corn and two rows of cowpea with the application of the goat manure 10 ton ha-1 increased land-use efficiency by 56%. Keywords: C-organic, productivity, revegetation, nutrient uptake, intercropping